GEN Z WORKFORCE RETENTION: COMPENSATION, SATISFACTION AND WORKLOAD - Khasanah, Kamalia Maulidatul; Reskiputri, Tatit Diansari; Murtaliningtyas, Wenny (Univesitas Muhammadiyah Tangerang, 2025)
Human resources are an important element in supporting the smooth operation of an organization. Human resources have a major role in the company because they are the drivers of policies and operational activities Most of today's productive age is dominated by millennials and generation Z who tend to have a dynamic lifestyle and an interest in exploring new experiences because they have a nature that always wants to achieve satisfaction. This study aims to find out and analyze the influence of workload, compensation, and job satisfaction on the loyalty of Gen Z employees in Ud. Karlita Macrame Banyuwangi. This type of research uses a quantitative method with a sample of 60 employees who are included in the Gen Z category and uses a Nonprobability sampling technique with a saturated sampling technique using a data collection technique in the form of questionnaires to respondents. The data analysis techniques of this study use instrumental testing, classical assumptions, multiple linear regression, hypothesis and determination coefficient. The results of the analysis obtained show that workload, compensation, and job satisfaction have a positive and partially significant effect on the loyalty of Gen Z employees in Ud. Karlita Macrame Banyuwangi, and the results of the R2 Determination Coefficient test obtained an influence contribution rate of 77% and 23% influenced by other factors outside the study.